Differential gene expression in mutant mice overexpressing or deficient in the serotonin transporter: a focus on urocortin 1. - Fabre, V; Massart, R; Rachalski, A; Jennings, K; Brass, A; Sharp, T; Lesch, K; Lanfumey, L; Hamon, M (2011)
Transcriptome analyses were performed in the anterior raphe area of mutant mice deficient in the serotonin transporter (5-HTT KO) or overexpressing this protein (5-HTT TG), which exhibit opposite changes in anxiety-related behavior. Among genes with altered expression, the gene encoding the neuropeptide urocortin 1 was down-regulated in 5-HTT KO and up-regulated in 5-HTT TG mice. Expression of the gene encoding cocaine-and-amphetamine-related-peptide, which colocalizes with urocortin 1, was also increased in 5-HTT TG mutants. Real-time RT-PCR confirmed these data and immunoautoradiographic labeling showed that parallel changes in neuropeptide levels were confined to the non-preganglionic Edinger-Westphal nucleus. Thus, 5-HTT expression correlates with that of urocortin 1, suggesting that this peptide can be involved in the behavioral changes observed in 5-HTT mutant mice.